Acculturation strategies employed by Malaysian students studying abroad - Ungku Mustaffa, Ungku Mazummar; Husin, Zamnah; Anuar, Nadia (Universiti Teknologi MARA, 2025)
Pursuing study overseas has always been one of the aspirations of Malaysian students to not only achieve their academic goals but also give them a chance to boost their intercultural communication competence in the long run. However, they often face various obstacles such as cultural barriers, academic strain, and psychological issues during their adjustment period. Therefore, acculturation strategies may be adopted to overcome various obstacles while learning abroad. Hence, this research aims to investigate the acculturation strategies employed by Malaysian international students studying abroad to overcome cultural conflicts. In this qualitative study, an in-depth interview was conducted with 6 Malaysian female students, specifically, 3 students from the United Kingdom and 3 students from Egypt, explores three key aspects: the preparations taken to study abroad, acculturation conflicts faced in the respective host countries and the acculturation strategies adopted by the students. The findings indicate that Malaysian students studying in the United Kingdom opted for an integration strategy while adjusting to the host culture. Two out of three participants studying in Egypt chose the integration strategy, whereas only one student adopted the separation strategy. It can be concluded that Malaysian students in the United Kingdom are more inclined to integrate to the Western culture compared to the students in the Eastern country (Egypt). The study offers recommendations for policymakers, higher education institutions, and prospective international students to enhance cross-cultural adaptation strategies.